(untitled) - Shimazaki, H. T. (London, 1992)
The service sector occupies a dominant position in the Japanese economy yet few have looked at the way the industry has developed. H.T. Shimazaki focuses on the growth and development of a major world security and communications corporation, SECOM. The success of the company has been rooted in the management strategies of Makoto Iaida who has developed the company from a small localized business to an international industry at the forefront of innovation. The author first looks at the background of Makoto Iaida, offering an insight into the nature of an entrepreneur and the issues this raises within the context of Japanese management styles. Then following the development of the company stage by stage, he assesses the importance of individual creativity in adapting and implementing traditional management techniques. He shows how strategies for human resources, service quality, new technology, globalization and corporate restructuring evolve within the context of a growing organization and includes an analysis of the innovative marketing techniques and product development processes needed to sell security services to one of the world's safest countries.
Keywords: Security systems industry,Telecommunication equipment industry,Hệ thống an ninh công nghiệp,Công nghiệp thiết bị viễn thông; Management,Case studies,Management,Case studies,Quản trị,Trường hợp nghiên cứu,Quản trị,Trường hợp nghiên cứu; Japan,Japan,Nhật Bản,Nhật Bản